Collapsing Focal Segmental Glomerulosclerosis in Siblings With Compound Heterozygous Variants in NUP93 Expand the Spectrum of Kidney Phenotypes Associated With Nucleoporin Gene Mutations - Cason, Rachel K.; Williams, Anna; Chryst-Stangl, Megan; Wu, Guanghong; Huggins, Kinsie; Brathwaite, Kaye E.; Lane, Brandon M.; Greenbaum, Larry A.; D’Agati, Vivette D.; Gbadegesin, Rasheed A. (Frontiers in Pediatrics, 2022)
Background Focal segmental glomerulosclerosis (FSGS) is a major cause of end stage kidney disease, with the collapsing form having the worst prognosis. Study of families with hereditary FSGS has provided insight into disease mechanisms. Methods In this report, we describe a sibling pair with NUP93 mutations and collapsing FSGS (cFSGS). For each brother, we performed next generation sequencing and segregation analysis by direct sequencing. To determine if the variants found in the index family are a common cause of cFSGS, we screened 7 patients with cFSGS, gleaned from our cohort of 200 patients with FSGS, for these NUP93 variants as well as for APOL1 high-risk genotypes. Results We identified segregating compound heterozygous NUP93 variants(1) c.1772G>T p.G591V, 2) c.2084T>C p.L695S) in the two brothers. We did not find these variants in the seven patients with cFSGS from our cohort, and as expected five of these seven patients carried the APOL1 high-risk genotype. Conclusion To the best of our knowledge, this is the first report of cFSGS in patients with NUP93 mutations. Determining the mechanisms by which these variants cause cFSGS may provide insight into the pathogenesis of the more common primary and virus-mediated forms of cFSGS.